The growing use of emerging digital technologies in administrative procedures: From automated administrative actions to algorithmic transparency (Forseti. Law Review, 2025)
This article analyzes the use of emerging technologies by the Public Administrationinordertofacilitate the access anduseofits services tocitizens through automated administrative actions and automated administrative procedures (with the possibility of using artificial intelligence).
Keywords: Metaverse; Artificial Intelligence; Automated Administrative; Algorithmic Transparency; Automatic Administrative Processing